Principals’ Fund Management Strategies and School Administrative Effectiveness - Olaifa, Adeseko Sunday; Ajala, Sodiq; Olaifa, Ebunlomo Oreoluwa; Medupin, Abiodun Johnson; Adeoye, Moses Adeleke (Indonesian Journal of Educational Research and Review, 2024)
A lack of prudence and mismanagement of school funds by the principals could give rise to poor student performance since it might slow down the acquisition of essential materials for teaching and learning. This study analyzes the relationship between principals’ fund management strategies and school administrative effectiveness. It assessed principals' budgetary practices, the perceived level of administrative effectiveness, and the relationship between fund management on secondary schools' effectiveness. Two research questions and one hypothesis were generated for the study. The research design was the descriptive survey type. The population of the study comprised all the one hundred and thirty-two (132) secondary schools. The total number of respondents included forty (40) principals representing 30% of the population, who were selected using the stratified random sampling technique. A self-designed questionnaire titled "Principals’ Fund Management Strategies and School Administrative Effectiveness in Secondary Schools Questionnaire (PFMSSAEQ)" was used for data collection, and Pearson's Product Moment Correlation Coefficient (r) yielded a reliability coefficient of 0.76. The results showed that principals kept accurate records of expenditure, had an average level of effectiveness, and had a significant influence on fund management in secondary schools. It was recommended that principals be strictly monitored by the Ministry of Education to ensure that they continue to maintain accurate record-keeping because of its role in effective fund management in secondary schools.